Business Model Design of a Digital-Based Outfit Recommendation Application for Fashion Personalization - Wahyudi, Nayla Nakeisha; Ariyani Mutiah Safitri; Darmadi, Anastasia Bella Clarisa; Ridho Aulia Rihhadatul Hudai; Petrus Sokibi (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2026)
The rapid development of the digital fashion industry has increased the demand for personalization in outfit and makeup selection, particularly among Generation Z and millennial women who face time constraints and demonstrate growing awareness of sustainability. Common issues include difficulties in matching clothing according to personal characteristics, low self-confidence due to inappropriate outfit choices, and a tendency toward overconsumption influenced by fast fashion practices. This study aims to design a business model and develop a user interface prototype for the ColorMatch application as an AI-based outfit recommendation platform, utilizing the Business Model Canvas (BMC) framework and the Prototyping development method. A descriptive qualitative approach is employed to analyze the nine elements of the BMC, while the prototyping stages include requirement identification, wireframe design, mockup development, and feedback-based evaluation to produce a user-oriented UI/UX design. The results indicate that ColorMatch offers a value proposition in the form of outfit and makeup recommendations based on seasonal color analysis, mood-based styling, and personal wardrobe optimization. The integration of digital business model approaches, AI technology, and UI/UX design through prototyping results in a platform that is economically viable, responsive to user needs, and supportive of sustainable fashion practices.